M-CRM on Cloud Computing by (m-learning) - khozouie, nasim; Fotouhi-Ghazvini, Faranak (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Todays ,organization want to provide the best possible experience to each and every customer, every time and every where they engage with organization . organizations want to know each customer inside and out, and empower every individual in businesses to deliver consistent, top-notch customer experiences . All this is possible with m-CRM investment. In this paper we describe how Implementation CRM by m-learning tools. But The implementation of m-learning need to enterprise m-LMS that expensive and Very complicated .In order to decrease cost and complexity , m-learning can Launch on cloud computing.